FIQH SIYASAH PERSPEKTIF KH AFIFUDDIN MUHAJIR DAN RELEVANSINYA DI INDONESIA - Muhammad Riyadi; Abdul Kholiq Syafa’at (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
The debate regarding the relationship between state and religion, particularly in the context of Islam, continues to evolve without an explicit guideline. There are three main schools of thought on the relationship between religion and state: secularistic, integralistic, and symbiotic. The secular approach proposes a separation between religion and state, while the integral approach emphasizes that the state should be governed by Islamic law. On the other hand, the symbiotic approach asserts that religion and state are mutually dependent. KH Afifuddin Muhajir highlights Pancasila as a relevant solution, accommodating Indonesia's diversity while bridging secularism and theocracy. In this context, KH Afifuddin Muhajir explains that the state is not the ultimate goal but rather a means to achieve the well-being of the people and uphold ethical values. This research employs a literature review and interviews with KH Afifuddin Muhajir, analyzing his thoughts and their relevance in the Indonesian socio-political context. The findings show that KH Afifuddin Muhajir thoughts offer a constructive perspective in addressing national challenges in the modern era, making his Fiqh Siyasah discourse highly relevant for further exploration.